Characteristics of the extra-man offence in water polo at the 2016 Olympic Games - Suga, M.; Enomoto, I.; Minami, T. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
This study examined the characteristics of each team`s extra-man offence by analysing data of 605 instances of extra-man formation at the 2016 Olympics. Game videos were reviewed, and a principal component analysis was conducted on several variables (i.e., shot results, the direction of the final pass before a shot, shooting position, faking before the shot, and on whether a defence player had a hand up to attempt a shot block). Two principal components, scattering of the defensive formation and shooting motion, were extracted. The characteristics of the extra-man offence were classified into four clusters (i.e., CL1 - CL4) based on the final pass course, shooting position, and shooting motion, and the strategies of each team`s extra-man offence were analysed. CL1 comprised one-motion shots after a parallel pass (success rate not high). CL2 comprised shots played after the defensive formation was scattered (high success rate, strategy adopted by Australia, the United States, Croatia, Spain, Greece, and Serbia). CL3 comprised a specific shooting technique from the top position, that is, when a player had to shoot because an excluded player was ready to return (strategy used by Australia, Japan, France, and Hungary). CL4 comprised shots after a faking motion from the side position (a common technique used by Montenegro, France, and Serbia). The extra-man offence in the high-ranked team was frequent in CL 2 with many shots played by faking from side position. Thus, techniques to scatter defensive formations were clarified and characteristic strategies of each team`s extra-man offence were examined.